SME Valley of Death: The Urgent Understanding, Differentiation, and Application of Strategic Thinking and Strategic Planning - Casanueva-Yánez, Galvarino; Ramos-Paredes, Juan; Rivera-Castañeda, Patricia Margarita; Pérez-Vargas, Reina; Abad-Paguay, Andrés Vicente; Cherres, Blanca Mercedes Verdezoto; Ibarra-Sandoval, Fredy; Rengifo-Lozano, Raúl (Journal of Ecohumanism, 2024)
This paper presents a study and comparative analysis of the concepts of strategic thinking and strategic planning. It is based on studies by different authors, thus making it possible to understand the importance of these terms and to grasp their correct application in companies. This allows managers and owners of SMEs, as well as entrepreneurs in general, to project both organizations or future ventures in a sustainable way over time. This enables the avoidance of mortality in the valley of death through the development of technological discoveries planned from the business philosophy. This presents a significant challenge for SMEs, whether small or medium-sized enterprises, in terms of the manufacture and implementation of correctly articulated action plans, as well as the construction of ideal scenarios for growth and development that benefit all the agents involved, through the generation of competitive advantages. In other words, the objective is to enable SMEs to achieve the basic financial goal that leads them to grow and be competitive in the market through strategic thinking planning, and technological innovation. This design of strategies is oriented towards enabling SMEs to see it materialize. This research project forms part of the doctoral thesis of one of its authors, who holds a PhD in Management Administration from the Benito Juárez G. University. It seeks to elucidate the elevated mortality rate of small and medium-sized enterprises (SMEs) in the town of Melipilla, Chile, and to facilitate the establishment and growth of this type of organization through a: The value proposition is defined as follows: A Business Solution Model for Chilean SMEs.